Female employees' perceptions of organisational support for breastfeeding at work: findings from an Australian health service workplace - Weber Danielle; Janson Anneka; Nolan Michelle; Wen Li; Rissel Chris (BMC, 2011)
Abstract Background Women's return to work can be a significant barrier to continued breastfeeding. Workplace policies and practices to promote and support continued, and longer duration of, breastfeeding are important. In the context of the introduction of a new breastfeeding policy for Area Health Services in New South Wales, Australia, a baseline survey was conducted to describe current practices and examine women's reports of perceived organisational support on breastfeeding intention and practice. Methods A cross sectional survey of female employees of the Sydney South West Area Health Service was conducted in late 2009. A mailed questionnaire was sent to 998 eligible participants who had taken maternity leave over the 20-month period from January 2008 to August 2009. The questionnaire collected items assessing breastfeeding intentions, awareness of workplace policies, and the level of organisational and social support available. For those women who had returned to work, further questions were asked to assess the perceptions and practices of breastfeeding in the work environment, as well as barriers and enabling factors to combining breastfeeding and work. Results Returning to work was one of the main reasons women ceased breastfeeding, with 60 percent of women intending to breastfeed when they returned to work, but only 40 percent doing so. Support to combine breastfeeding and work came mainly from family and partners (74% and 83% respectively), with little perceived support from the organisation (13%) and human resources (6%). Most women (92%) had received no information from their managers about their breastfeeding options upon their return to work, and few had access to a room specially designated for breastfeeding (19%). Flexible work options and lactation breaks, as well as access to a private room, were identified as the main factors that facilitate breastfeeding at work. Conclusions Enabling women to continue breastfeeding at work has benefits for the infant, employee and organisation. However, this baseline study of health employees revealed that women felt largely unsupported by managers and their organisation to continue breastfeeding at work.